1987
DOI: 10.1161/01.str.18.2.482
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of endothelium-dependent vasodilation induced by acetylcholine and adenosine triphosphate following experimental subarachnoid hemorrhage.

Abstract: The effect of subarachnoid hemorrhage (SAH) on endotbelium-dependent vasodilation of isolated rabbit basilar artery was examined using an isometric tension recording method. Thirty-five rabbits that had 2 successive blood injections were divided into 3 groups: normal animals (control), 4 days, and 3 weeks after the first SAH. Acetylcholine (ACh) (10~6-10~4 M) and adenosine triphosphate (ATP) (10~6-10~4 M) were used to evoke dose-dependent vasodilation of isolated arterial rings previously contracted by 10~6 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…However, in a double-injection model, responsiveness to both stimuli was reduced. 12 In addition, Kim et al 10 have reported that endothelium-dependent cerebrovascular relaxation in response to vasopressin and thrombin is reduced by the double-injection method in dogs, while other such responses to many other stimuli are preserved. Further, Svendgaard, et al 13 found that cerebrovascular dilation in response to arterial hypercapnia is attenuated in the presence of perivascular blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a double-injection model, responsiveness to both stimuli was reduced. 12 In addition, Kim et al 10 have reported that endothelium-dependent cerebrovascular relaxation in response to vasopressin and thrombin is reduced by the double-injection method in dogs, while other such responses to many other stimuli are preserved. Further, Svendgaard, et al 13 found that cerebrovascular dilation in response to arterial hypercapnia is attenuated in the presence of perivascular blood.…”
Section: Discussionmentioning
confidence: 99%
“…6 -7 In adult animal models of ICH, the perivascular presence of blood alters cerebrovascular responsiveness. 8 - 12 In particular, responses involving endothelium-derived relaxing factor (EDRF) and arterial hypercapnia 13 can be reduced. On the other hand, little is known concerning the effects of perivascular blood on dilator responses of the cerebral circulation in neonates.…”
Section: Ntracranial Hemorrhage (Ich) Is a Serious Problemmentioning
confidence: 99%
“…One possible explanation is that the vascular damage produced by SAH may not be enough to promote the impairment of CGRP-induced vasodilation. Nakagomi et al 21 previously demonstrated that endothelium-dependent relaxation by acetylcholine was not impaired in the basilar artery of a rabbit sacrificed after a single injection of blood but that it was impaired in a rabbit sacrificed after two injections of blood. In spite of the possibility of conflicting results due to different models, it is likely that the presynaptic mechanism may be disturbed after SAH but that the postsynaptic mechanism may not be disturbed during the course of SAH in our model.…”
Section: Figure 5 Typical Pattern Of Effect Of Different Concentratimentioning
confidence: 98%
“…One of the prongs was fixed and attached to the computer system (DI-190 portable I/O module; Dataq Instruments, Akron, Ohio, U.S.A.) for real-time recording and the other prong was moved apart slowly to stretch the artery segment. This procedure was done several times in one hour to produce a steady resting tension of 0.4 g. 17,24) The buffer was changed every 10 minutes. Then 100 ml KCl (40 mM concentration) was added to the bath to achieve KClinduced steady contraction.…”
Section: Steady Resting Tensionmentioning
confidence: 99%
“…Local concentrations of NO are also reduced due to the high binding affinity with oxyhemoglobin (oxyHb) derived from the subarachnoid clot around the brain surface and major blood vessels. 16,17) NO is involved in the regulation of the cerebral circulation, and is accepted as the most effective relaxing agent for the cerebral arterial network, and participates in the maintenance of resting cerebrovascular tone. 7,8) Depletion of NO is thought to be important in the pathogenesis of cerebral vasospasm.…”
Section: Introductionmentioning
confidence: 99%